COMPETENCE-TARGETED LEARNING OF RUSSIAN AS A FOREIGN LANGUAGE WITHIN THE COURSE “LANGUAGE OF THE PR SPECIALTY” - Lazarev , Sergey; Asonova , Galina; Buyskikh, Tatyana (Revista Inclusiones, 2021)
The article makes up the case for the competence-targeted learning in the system of language training for international students majoring in PR. Language acquisition for special purposes is a difficult task facing non-native learners. It is possible to achieve high results only in the case of gradual, student-centered learning.